Предмет: Алгебра,
автор: mazinadachenka
а⁹-b³
решите пожалуйста по формуле а³-b³=(a-b)(a²+ab+b²)
Ответы
Автор ответа:
1
Ответ:
а⁹-b³=(a³-b)(a⁶+a³b+b²)
Объяснение:
а⁹-b³
а³-b³=(a-b)(a²+ab+b²)
а⁹-b³= (a³)³-b³=(a³-b)(a⁶+a³b+b²)
mazinadachenka:
спасибо большое
Автор ответа:
1
Ответ:
Так как 8= 2^3
x^3+8=(x+2)(x^2-2x+4)
Объяснение:
Похожие вопросы
Предмет: Русский язык,
автор: fila3
Предмет: Қазақ тiлi,
автор: danbat00
Предмет: Українська мова,
автор: 5428Соломія1
Предмет: Қазақ тiлi,
автор: melissa1825